Réponses

2013-12-02T23:42:30+01:00
A = (x+1)²+(x-3)²
A = x²+2x+1+x²-6x+9
A = 2x²-4x+10

B = (3-x)²+(x+5)²
B = 9-6x+x²+x²+10x+25
B = 2x²+4x+34

C = (x-2)²+(x+4)(x-4)²
C = x²-4x+4+(x+4)(x²-8x+16)
C = x²-4x+4+x³-8x²+16x+4x²-32x+64
C = x³-3x²-20x+68

D = (x+1)(x-1)+(x+4)²
D = x²-x+x-1+x²+8x+16
D = 2x²+8x+15

E = (x-5)²+(2x+7)(2x-7)
E = x²-10x+25+4x²-14x+14x-49
E = 5x²-10x-24
2013-12-03T01:58:03+01:00
A = (x + 1)² + (x-3)² = x^2+2x+1+ x^2 - 6x + 9 = 2x^2 - 4x +10 = 2*(x^2-2x+5)

B = (3 - x)² + (x+5)² = 9 - 6x +x^2 + x^2 + 10x +25 = 2 x^2 + 4x + 34 = 2* ( x^2+2x+17)

C = (x - 2)² + (x + 4)(x - 4)²= x^2 -4x +4 + ((x^2-16) (x-4)) = x^2-4x+4 + x^3-4x^2-16x+64 = x^3 - 3x^2 -20x +68 = x( x^2 -3x -20) +68

D = (x + 1)(x - 1) + (x + 4)² = x^2 -1 + x^2 +8x +16= 2x^2 + 8x + 15 = 2x (x+4) +15

E = (x - 5)² + (2x + 7)(2x - 7)
Dslee, E = x^2 -10x +25 + 4x^2 -49 = 5 x^2 -10x -24